KARAKTERISTIK MANGGA LOKAL (Mangifera spp) MELALUI IDENTIFIKASI MORFOLOGI DAN ANATOMI DI KABUPATEN DONGGALA DAN KABUPATEN SIGI - Faizal Faizal; Mahfudz Mahfudz; Enny Adelina (Agroland: Jurnal Ilmu-ilmu Pertanian, 2017)
This study aimed to assess the characteristics of local mango plants based on their                       leaf morphology and anatomy.  The morphological observations were conducted in Funta                  Sindue,of Donggala district and Oloboju Sigi Biromaru of Sigi district while the anatomy was     determined in the Biotechnology Laboratory at Faculty of Mathematics and Natural Sciences of Tadulako University from January to April 2016. The morphological parameters observed were plant age, plant height, stem diameter, canopy diameter, canopy shape and stemcolor whilst the variable sof leaf  anatomy  were stomata size, epidermis size, stomata number, epidermis number, stomata density and stomata  index. The morphological and anatomical characters observed by a cluster analysis were described in  the form of a dendogram. The results of cluster analysis of both villages at a distance of    0540 resulted  in three accessions which are OB12, OB13 and OB15. The OB13 was found to have   highest stomata   index and stomata density while the OB12 has the lowest ones. The OB15 also has lowest stomata density.Keywords : Dendogram,  Mango, Morphology, Leaf anatomy.